2022
DOI: 10.1073/pnas.2116136119
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilafemales have an acoustic preference for symmetric males

Abstract: Significance Theoretically, symmetry in bilateral animals is subject to sexual selection, since it can serve as a proxy for genetic quality of competing mates during mate choice. Here, we report female preference for symmetric males in Drosophila , using a mate-choice paradigm where males with environmentally or genetically induced wing asymmetry were competed. Analysis of courtship songs revealed that males with asymmetric wings produced songs with asymmetric fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The reduction of larval crawling in the 1 and 0.001 mM applications compared to that in the control group was found to be statistically significant. Kumar et al [ 48 ] exposed Drosophila larvae to the pesticide Retenone and evaluated the larval creep activity and pattern. In parallel with our study, they found a decrease in the larval crawling activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of larval crawling in the 1 and 0.001 mM applications compared to that in the control group was found to be statistically significant. Kumar et al [ 48 ] exposed Drosophila larvae to the pesticide Retenone and evaluated the larval creep activity and pattern. In parallel with our study, they found a decrease in the larval crawling activity.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing auditory features of these side-specific bouts revealed asymmetry in the songs produced by the rejected males with asymmetric wings (Vijendravarma et al, 2022). Although Drosophila courtship song has been investigated extensively since its discovery in 1962 (Shorey, 1962), this bilaterality had been ignored.…”
Section: Auditorymentioning
confidence: 99%
“…Former studies in this field across taxa are also biased toward investigating visual assessment of male FA and we argue that this could be one of the factors contributing toward the observed heterogeneity. Support for this idea comes from our recent study that reports how Drosophila melanogaster females discriminate asymmetrically winged males during courtship based on the asymmetric songs (auditory cues) they produced (Vijendravarma et al, 2022). Rather than validating this hypothesis, this review aims to examine mate choice literature for potential non‐visual cues and other indirect methods that females could utilize to either detect FA in courting males (directly or indirectly) or discriminate against asymmetric individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations